Mycoflora and natural occurrence of aflatoxins and fumonisin B1 in cassava and yam chips from Benin, West Africa - Gnonlonfin, G.J.B.; Hell, K.; Fandohan, P.; Siame, A.B. (Elsevier, 2008)
The presence of fungi, aflatoxins and fumonisin B1 in cassava and yam chips (during 28 processing and storage) were evaluated during two consecutive seasons in two agroecological zones of Benin (Northern Guinea Savannah, NGS and Sudan Savannah, SS). The Benin samples were assessed for moisture content, fungal infestation and total aflatoxin and fumonisin B1 contamination. During the two seasons, samples collected from the NGS, had moisture contents ranging from 10.0 to 14.7% in cassava chips and from 11.4 to 15.3% in yam chips. In samples from the SS, moisture content ranged from 10.1 to 14.5% and 11.1 to 14.5% in cassava and yam chips, respectively. A. flavus was the predominant fungal species. The maximum cfu/g in cassava and yam chips was 8950 and 6030, respectively. Other fungal species isolated included P. chrysogenum, M. piriformis, Phoma sorghina, F. verticillioides, R. oryzae and Nigrospora oryzae. High performance liquid chromatography analysis of both cassava and yam chips showed no contamination by either aflatoxins or fumonisin B1.